Using Google Scholar Citations to Profile Scholars' Work - Linda M. Galloway; Anne E. Rauh (Issues in Science and Technology Librarianship, 2014)
The article offers a guide for librarian authors to developing their own Google Scholar Citations profile which would allow them to showcase and promote their academic products and help them connect with experts and potential collaborators. An overview of the Google Scholar Citations app is provided. It outlines steps for optimizing or highlighting one's research with Google Scholar Citations.